Achieving food security in the face of climate change - Ruth Delzeit; Kacana Sipangule; Rainer Thiele (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2015)
The year 2015 is important for sustainable development: the Millennium Development Goals (MDGs) have expired and have been replaced by the Sustainable Development Goals (SDGs) in September, and from November 30th to December 11th, the 21st Session of the Conference of the Parties to the United Nations Framework Convention on Climate Change (COP21/CMP11) will be held. The COP21/CMP11 aims to reach a universal, legally binding agreement to combat climate change and boost the transition towards resilient, low-carbon societies and economies. Reducing greenhouse gas emissions to limit global warming (mitigation) and helping societies adapt to existing climate change are seen as measures the agreement should equally focus on. The group that is likely to suffer most from climate change is poor rural households in developing countries who mainly rely on small-scale agriculture for their livelihood. In large parts of Sub-Saharan Africa and South Asia, the two regions with the highest incidence of undernutrition, the MDG of cutting hunger by half has not been met (United Nations 2014). Reaching the still more ambitious SDG 2 (end hunger until 2030, achieve food security and improved nutrition, and promote sustainable agriculture) appears to be a daunting task even in the absence of climate change. By lowering agricultural yields in some regions, climate change adds to the challenge. This policy brief therefore argues for a particular focus on agricultural production and food security in the current COP21 to help the largest possible number of people satisfy the most basic need of being well nourished.
Keywords: 330